Regional Partnership Program in Developing of Potential Agricultural Resource Based on Integrated Agricultural Technology in Buol Distric - Nur Hayati; . Najamudin; . Sulaeman; Sri Anjar Lasmini (Institut Pertanian Bogor, 2018)
Lakea Sub-district, Buol District has a wealth of natural resources (SDA) potential in the form of large and fertile plains area that can be developed into agricultural land for food crops and horticulture, areas with hilly topography can be developed various types of plantation commodities, forest resources that can be cultivated MPTS and marine potential. To optimize the potential of natural resources is needed integrated agricultural technology that can be applied by the community. Regional partnership program aims to assist the community in exploiting the potential of natural resources owned by kindly and wisely through integrated agricultural technology innovation to improve their welfare. PKW is implemented in two villages in Lakea Sub-District, Lakea I and Ngune Village. The methods used in the implementation of the program include: training, plot demonstration technology, guidance, and community assistance. The results of the program implementation showed that the adoption of technology was good enough from the target community group which is showed by the transfer of technology in the development of SRI rice cultivation with legowo row planting system, the development and entrepreneurship of local-made production facilities include bioinsecticide development Beauveria bassiana, Trichoderma sp biofungicide, liquids organic fertilizer and granules, development of PKW production facilities, and development of forage grazing garden with Panicum sarmentosum grass cultivation. The technology assembly is as the result of a suitable PKW team study to be developed in the Lakea District of Buol Regency in utilizing and developing the potential of natural resources in the program target location. Results of demonstration plot of rice cultivation of SRI with legowo 2:1 row planting system resulted in rice production of 4.7 t ha-1 higher than the conventional were 3.5 t ha-1.